BURDEN OF POLYCYSTIC OVARIAN SYNDROME AMONG ADOLESCENTS AND YOUNG WOMEN IN INDIA: A COMPREHENSIVE SYSTEMATIC REVIEW - Abdiyeva, M.O.; Dwivedi, K. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Polycystic ovarian syndrome (PCOS) is one of the most common endocrine and metabolic disorders among adolescent girls and young women. Characterized by hyperandrogenism, menstrual dysfunction, and polycystic ovarian morphology, PCOS is associated with long-term health complications such as insulin resistance, type 2 diabetes mellitus, cardiovascular diseases, and psychological disturbances. Despite its growing prevalence, awareness and early diagnosis of PCOS in India remain inadequate. Objective: This systematic review aims to assess the prevalence, risk factors, clinical presentations, and awareness levels of PCOS among adolescent girls and young women in India. Methods: A systematic literature search was conducted following PRISMA 2020 guidelines across PubMed, Scopus, ScienceDirect, and Google Scholar databases. Studies published between 2010 and 2024 involving Indian populations aged 11 to 30 years were included. Data were extracted regarding study characteristics, diagnostic criteria, PCOS prevalence rates, associated risk factors, and levels of awareness. Results: Seven studies involving 267 to 1068 participants each were included. The reported prevalence of PCOS among Indian adolescents varied widely, ranging from 6% to 77.1%, depending on diagnostic criteria and study methodology. Obesity (odds ratio [OR]: 3.09), insulin resistance (OR: 2.12), hypertension (OR: 4.46), family history, and psychological stress were consistently identified as significant risk factors. Awareness regarding PCOS was found to be critically low, with over 78% of adolescents unaware of the syndrome’s symptoms and long-term complications in some studies. Menstrual irregularities, hyperandrogenic features, and emotional disturbances were common clinical presentations across studies. Conclusion: PCOS presents a substantial public health challenge among Indian adolescents and young women. There is an urgent need for improved awareness initiatives, early metabolic screening, lifestyle interventions, and standardized diagnostic protocols to facilitate timely identification and management of PCOS. Future research should focus on longitudinal studies and targeted public health strategies to mitigate the rising burden of PCOS-related complications in India.